APLIKASI PUPUK ECO FARMING DAN PENAMBAHAN GIBERELIN TERHADAP PERTUMBUHAN BAYAM MERAH (Amaranthus tricolor L.) PADA SISTEM WALL PLANTER BAG - Syafira, Zara; Idris, M.; Rahmadina (Jurnal Biogenerasi, 2024)
Based on the Central Statistics Agency (2022), red spinach production is said to be unstable at this time. The application of eco farming and gibberellins as well as utilizing the home environment to use a wall planting bag planting system is one strategy to overcome this problem. The aim of this research is to determine the correct dosage for the growth of red spinach plants planted using a wall planter bag system. This research was conducted in September-October 2023. This research used a factorial randomized block design, namely E0 (control), E1 (8 ml/l), E2 (16 ml/l) and E3 (24 ml/l) with G0 (control , G1 (200 ppm) and G2 (250 ppm). Based on the observations made, the combination treatment had a significant effect on plant height and leaf area, but had no effect on plant fresh weight. The E3G2 treatment was the most effective dose in this study.